GIROLAMO SAVONAROLA AND THE BEGINNING OF THE POLITICAL REFORM IN FLORENCE IN 1494 - E. P. Telmenko (Гуманитарные и юридические исследования)
The article analyzes the correlation between Girolamo Savonarola's participation in the political reform in Florence in the late 15th century and his prophetic mission, as well as his ideas on the spiritual reform of the Church and society. The beginning of the French military campaign in Italy and the proscription of Piero de'Medici from Florence in November 1494 contributed to increasing the influence of Savonarola in the political life of the city. His sermon on the need for a spiritual reformation, based on the observance of the evangelical commandment of love for God and one's neighbour, is organically combined with the repose of the «public good» as the policy basis. Consequently, according to the prophet, the moral perfection of citizens must ensure the observance of the «public good» principle in social life, and the law of universal peace and the establishment of the Great Council must become its practical implementation.